2020
DOI: 10.14314/polimery.2020.7.8
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable polymer composites based on polylactide used in selected 3D technologies

Abstract: As part of the work, new polymer materials were used in 3D printing, which can be used in three technologies depending on the apparatus used: Fused Filament Fabrication (FFF), Melted and Extruded Manufacturing (MEM), Melt Extrusion Polymers (MEP). As part of the work, the properties of obtained polymer composites were examined. Polylactide (PLA) was used as the matrix, and powdered natural ground fillers were used as fillers: bamboo dust (PB), cork dust (PK) and wood dust (PD). In the first part of the work, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 12 publications
3
7
0
1
Order By: Relevance
“…It is consistent with the previously reported works that the forsythia suspensa extract could effectively enhance the processing stability of the polyethylene matrix 42 . In addition, it is reported that the natural filler could increase the fluidity of the matrix by 48.73% compared to unfilled polylactic acid, and the load, the shape of the filler, and the interaction between the filler and the matrix could influence the fluidity of polymer matrix, further affecting its processing performance 58,59 . These results demonstrated the capability of the SBE to improve the processing performance of PBAT.…”
Section: Resultssupporting
confidence: 91%
“…It is consistent with the previously reported works that the forsythia suspensa extract could effectively enhance the processing stability of the polyethylene matrix 42 . In addition, it is reported that the natural filler could increase the fluidity of the matrix by 48.73% compared to unfilled polylactic acid, and the load, the shape of the filler, and the interaction between the filler and the matrix could influence the fluidity of polymer matrix, further affecting its processing performance 58,59 . These results demonstrated the capability of the SBE to improve the processing performance of PBAT.…”
Section: Resultssupporting
confidence: 91%
“…The use of models allows for avoiding many unnecessary operational errors. However, it is required to conduct further research processes, which allow for the development of biodegradable materials [ 71 , 72 , 73 ] and reflect the structure and strength of human bone as accurately as possible [ 74 , 75 ], because the models presented in the article had a susceptibility to cutting and milling that was different from natural bone. When planning the procedure, the models presented in the article were made of classic polymer materials, for which it was difficult to perform efficient cuts and drilling due to their plastic deformation.…”
Section: Discussionmentioning
confidence: 99%
“…The thermal stability is unaffected by the addition of Micro cellulose and MAH. Bulanda et al [ 126 ] compared the mechanical properties of PLA/Bamboo Dust/ cork dust/ wood dust with 3D printing and Injection molding. The composite was made using a twin screw extruder using 69% PLA, 30% fillers, and 1% compatibilizer.…”
Section: Fdm Compositesmentioning
confidence: 99%